KEWENANGAN DEWAN KEHORMATAN PENYELENGGARA PEMILU (DKPP) DALAM PENEGAKAN ETIKA PENYELENGGARA PEMILU - Herfein Bria; Erikson Sihotang; Kadek Merry Herawati (Yayasan Nusantara Hasana Berdikari, 2024)
The purpose of this study is to find out and analyze the Authority of the Honorary Council of Election Organizers (DKPP) in the enforcement of the code of ethics of General Election organizers and to find out the Authority of the Honorary Council of Election Organizers (DKPP) in Resolving General Election Violations by Members of the General Election Commission. The method used is a juridical-normative approach that focuses on the literature materials and regulations used as the basis for the preparation. The result of this research is that DKPP was formed to enforce the code of ethics which is one of the triumvirates of election organizers. The existence of coercive authority owned by the DKPP is to ensure that the Election Organizers obey the Code of Ethics. The existence of a Code of Ethics for Election Organizers, as a rule of the game for Election Organizers in carrying out their duties and functions during the implementation of elections, as mandated in Article 22E paragraph (1) of the 1945 Constitution of the Republic of Indonesia, namely elections are carried out directly, publicly, freely, secretly, honestly and fairly. The code of ethics aims to maintain the independence, integrity, and credibility of all ranks of Election Organizers. Second, Law Number 15 of 2011 which regulates election organizers, has regulated the duties and authority of the DKPP in Law Number 15 of 2011 concerning General Election Organizers. And if the DKPP issues a Decision ordering the KPU to conduct a review to restore the constitutional rights of the Candidates for Members of the DPRD, which decision is not the authority of the DKPP, but the authority of the KPU. The Honorary Council of Election Organizers (DKPP) has exercised its authority in accordance with Law Number 15 of 2011 concerning General Election Organizers in resolving election violations committed by one member of the KPU.